Microscopic Polyangiitis Initially Presumed to Be Endocarditis - Takahiro Kaneko; Shunsuke Hino; Yosuke Iijima; Norio Horie (Case Reports in Dentistry, 2020)
The antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitides (AAVs), which include fever of unknown origin (FUO), are rare diseases characterized by necrotizing inflammation of small blood vessels and the presence of ANCAs. Microscopic polyangiitis (MPA) is a subtype of the AAVs. Although the prevalence of AAVs has generally increased over the last 20 years, there have been rare reports from the dental and oral surgery field. In this article, we present a case of MPA suspected to be infective endocarditis (IE) following tooth extraction.